POLITIK DAN KEMANUSIAAN: RELASI TUMPANG TINDIH DALAM PENANGANAN PENGUNGSI DI INDONESIA - Finahliyah Hasan (Universitas Riau Kepulauan, 2023)
ABSTRACT In a complex humanitarian crisis, where humanitarian assistance not only relies on humanitarian organizations but requires the involvement of the state, humanitarian practices can no longer refer to the basic principles of humanity which are considered apolitical. This article aims to show the overlapping relationship between political interests and humanitarian practices in the context of refugee crises in the non-signatory state of the global refugee regime. A qualitative approach is used as a method to provide interpretation of the data found where the main focus is on primary data and journal articles. It is expected that this article will provide a comprehensive picture of how political interests are associated with the effort of refugees protection during transit in non-signatory of refugee convention such as Indonesia. Although it is not obliged to accept refugees as a consequence of not having ratified the 1951 refugee convention and 1967 protocol, Indonesia is trying to adapt its domestic policies to various political considerations without ignoring the humanitarian aspect. However, in practice, Indonesian refugee handling is problematic because it is based not only on humanitarian concerns but also on the calculation of costs and benefits and the refugee framing. ABSTRAK Dalam krisis kemanusiaan yang kompleks, dimana asistensi kemanusiaan tidak lagi hanya mengandalkan organisasi-organisasi kemanusiaan tetapi memerlukan pelibatan negara, maka praktek kemanusiaan tidak lagi dapat mengacu pada prinsip dasar kemanusiaan yang diklaim apolitis. Artikel ini bertujuan untuk menunjukkan relasi tumpang tindih antara kepentingan politik dan praktek kemanusiaan dalam konteks krisis pengungsi di negara yang tidak menjadi bagian dari rezim pengungsi global. Pendekatan kualitatif digunakan sebagai metode untuk memberikan interpretasi atas data-data yang ditemukan dimana acuan utama fokus pada data primer serta artikel jurnal. Riset ini diharapkan dapat memberikan gambaran secara komprehensif bagaimana kepentingan politik berasosiasi dengan upaya perlindungan pengungsi selama transit di negara yang tidak meratifikasi konvensi pengungsi seperti Indonesia. Walaupun tidak memiliki kewajiban untuk menerima pengungsi sebagai konsekuensi belum meratifikasi konvensi pengungsi 1951 dan protokol 1967, Indonesia berupaya menyesuaikan kebijakan domestiknya dengan beragam pertimbangan politik tanpa mengindahkan aspek kemanusiaan. Namun pada prakteknya, penanganan pengungsi di Indonesia menjadi problematik dikarenakan bukan hanya kalkulasi cost and benefit tetapi framing terkait pengungsi itu sendiri.